Assessment of periodontal status of Indian police personnel of Central India: A cross-sectional representative study - Aishwarya Singh; Ajay Bhambal; Sudhanshu Saxena; Vidhatri Tiwari; Utkarsh Tiwari; Anupriya Singh (Wolters Kluwer Medknow Publications, 2015)
Background: Periodontal health is an integral part of oral and in turn general health. Police personnel form the pillars for safety and security of a community hence their health is of utmost importance. The present study aimed to assess the periodontal health status of district police personnel employed in police stations of Bhopal District of Central India. Materials and Methods: A cross-sectional study was conducted on all the available police personnel at various police stations. Final sample size comprised of 781 subjects. The data were recorded on modified World Health Organization format (1997) comprising Community Periodontal Index (CPI) and loss of attachment. Results: The mean age of subjects was 40.5 years, 95.6% were males and 4.4% were females. Regarding highest CPI score, 23.4% subjects had a healthy periodontium whereas maximum subjects (31.3) had a CPI score 2. The CPI scores showed a significant relationship with post, age and education. Conclusion: Overall periodontal status was poor with a high number of subjects requiring oral health education.